ANALYSIS OF WORK DURATION AND WORK LOAD WITH COMPLAINTS OF MUSCULOSCELETAL DISORDERS (MSDS) ON LAUNDRY WORKERS IN DUNGINGI DISTRICT THE CITY OF GORONTALO - Irwan Irwan; Juwita Suma; Tirsa Khairunisa Madjowa; Deliyana I Katili (International Journal of Health Science & Medical Research, 2023)
Musculoskeletal Disorders (MSDs) are disorders of the musculoskeletal system that cause symptoms such as pain. MSDs complaints occur in parts of the skeletal muscles that a person feels, ranging from very mild to very painful. The novelty of this research is that it examines the length of work and workload with complaints of Musculoskeletal Disorders (MSDs). This study aimed to analyze the relationship between work duration and workload with complaints of Musculoskeletal Disorders (MSDs) among laundry workers in Dungingi District, Gorontalo City. This study uses quantitative research with an analytic survey approach with a cross-sectional design. The sample in this study was 82 respondents, namely laundry workers with a working period of ≥ 2 years in Dungingi District, Gorontalo City. Data analysis using Chi-Square test analysis. The results show a relationship between the length of work and complaints of Musculoskeletal Disorders with a value (p = 0.006 0.05). There is also a relationship between workload and complaints of musculoskeletal disorders with a value (p = 0.007 0.05). In conclusion, the longer the duration of a person's work can increase the incidence of MSDs complaints, and the heavier the workload workers receive can raise MSDs complaints.